Manajemen Idarah Dalam Meningkatkan Kualitas Takmir Masjid Ki Marogan Kecamatan Kertapati Kota Palembang - Laili Maftuha; Candra Darmawan; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Idarah Management in Improving the Quality of Ki Marogan Mosque Takmirs, Kertapati District, Palembang City". The research conducted by the author is a qualitative approach. This study also used interview, observation and documentation data collection techniques. The data analysis techniques of this study are Data Reduction, Data Display and Concusing Drawing. The main data were obtained from interviews with mosque leaders and mosque worshippers. From the results of this study shows that the implementation of idarah masjid ki marrogant has not been carried out properly such as; Planning has not been carried out properly because there has been no deliberation to plan activities, organizing has not been carried out properly because the takmir has not carried out the duties and authorities that have been given and supervision has not been carried out properly because there is no evaluation of work programs to assess the results of activities. So it is advisable for the Takmir of Masjid Ki Marogan to be more responsible in handling matters related to the mosque in accordance with the duties that have been mandated.